2019
DOI: 10.1101/sqb.2019.84.040352
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Spatial Transcriptomes: Emerging Frontier for Understanding Gene Regulation

Abstract: RNAs are trafficked and localized with exquisite precision inside the cell. Studies of candidate messenger RNAs have shown the vital importance of RNA subcellular location in development and cellular function. New sequencing-and imaging-based methods are providing complementary insights into subcellular localization of RNAs transcriptome-wide. APEX-seq and ribosome profiling as well as proximity-labeling approaches have revealed thousands of transcript isoforms are localized to distinct cytotopic locations, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 164 publications
(194 reference statements)
0
10
0
Order By: Relevance
“…The biotinylated RNA could then be affinity purified with streptavidin beads and sequenced. The APEX-Seq approach was used to generate an atlas of human RNA localization covering nine different subcellular niches and to probe the spatial organization of transcripts associated with translation initiation complexes as well as repressive RNA granules ( 18 , 331 ). This study unveiled the dynamic, varied, and stress type–dependent nature of stress granules.…”
Section: Sequencing-based Methods In Spatial Transcriptomics and Prot...mentioning
confidence: 99%
See 2 more Smart Citations
“…The biotinylated RNA could then be affinity purified with streptavidin beads and sequenced. The APEX-Seq approach was used to generate an atlas of human RNA localization covering nine different subcellular niches and to probe the spatial organization of transcripts associated with translation initiation complexes as well as repressive RNA granules ( 18 , 331 ). This study unveiled the dynamic, varied, and stress type–dependent nature of stress granules.…”
Section: Sequencing-based Methods In Spatial Transcriptomics and Prot...mentioning
confidence: 99%
“…Spatial proteomics and transcriptomics have often been reviewed independently with technical details covered in previous articles ( 18 , 19 , 20 ). Here, we outline and directly compare methods (summarized in Table 1 ) that interrogate the spatial transcriptomic and proteomic within subcellular compartments of cells, rather than spatial information at the tissue level, and suggest gaps in technology in need of further advancement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both approaches utilizing fluorescent in situ hybridization with complex probe sets [38] and RNA localization by fractionation and sequencing [39] revealed that most mRNAs encoding membrane proteins were preferentially positioned at the membrane. Moreover, mRNAs encoding cytoplasmic and polar proteins were largely distributed throughout these respective cellular regions [40]. It is known that the cis-acting sequence in the transcript serves as a ZIP code [41] or signal recognition particle [38] that can determine protein targeting in a particular region through RNA localization.…”
Section: Organization Of Macromolecules At the Right Position Is Advantageous For Carrying Out Various Functions Effectivelymentioning
confidence: 99%
“…Furthermore, centrifugation-based techniques such as Grad-seq (gradient sequencing), CeFraSeq (cell fractionation sequencing) and R-DeeP (RNA-dependent proteins) exist, charting the global RNA-protein co-sedimentation landscape, the shuttling of RNA to subcellular fractions and the RNA-dependence of protein complexes, respectively [ 16 , 20 , 21 , 22 , 23 ]. Such approaches were recently summarized elsewhere [ 24 , 25 ] and are not reiterated in detail in the present review. Also, common molecular principles guiding lncRNA interaction with individual molecules (proteins, mRNAs and microRNAs) in the cytoplasm and nucleus have recently been reviewed [ 2 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%